Down-regulation of NCED leads to the accumulation of carotenoids in the flesh of F1 generation of peach hybrid - Song, Haiyan; Liu, Junhong; Chen, Chaoqun; Zhang, Yao; Tang, Wenjing; Yang, Wenlong; Chen, Hongxu; Li, Mengyao; Jiang, Guoliang; Sun, Shuxia; Li, Jing; Tu, Meiyan; et al. (Frontiers in Plant Science, 2022)
Flesh color is an important target trait in peach [Prunus persica (L.) Batsch] breeding. In this study, two white-fleshed peach cultivars were crossed [Changsong Whitepeach (WP-1) × ‘Xiacui’], and their hybrid F1 generation showed color segregation of white flesh (BF1) and yellow flesh (HF1). Metabolome analysis revealed that the flesh color segregation in the hybrid F1 generation was related to the carotenoid content. The decrease in β-carotene and β-cryptoxanthin in BF1 flesh and increase in β-cryptoxanthin oleate, rubixanthin caprate, rubixanthin laurate and zeaxanthin dipalmitate in HF1 flesh contributed to their difference in carotenoid accumulation. Transcriptome analysis demonstrated that compared with BF1, HF1 showed significant up-regulation and down-regulation of ZEP and CCD8 at the core-hardening stage, respectively, while significant down-regulation of NCED in the whole fruit development stage. The down-regulation of NCED might inhibit the breakdown of the violaxanthin and its upstream substances and further promote the accumulation of carotenoids, resulting in yellow flesh. Therefore, NCED may be a key gene controlling the fruit color traits of peach. In this study, targeted metabolomics and transcriptomics were used to jointly explore the mechanism controlling the fruit color of peach, which may help to identify the key genes for the differences in carotenoid accumulation and provide a reference for the breeding of yellow-fleshed peach.